TECHNIQUES OF HYPOPHYSECTOMY IN THE DOG SOME USEFUL MODIFICATIONS - RETANA POSADA, GUILLERMO; CARVAL HAES GONZALEZ, RODOLFO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1942)
Transtemporal technics are discussed, and a modification is descr in detail Novelties introduced are a relatively low arc for the primary incision, permitting more direct access to the gland; removal of only a part of the zygomatic process not the whole
REV SOC MEX HIST NAT
Keywords: TECHNIQUES, HYPOPHYSECTOMY, DOG, USEFUL MODIFICATIONS; CIENCIAS DE LA VIDA